Hydraulic erosion in different tillage systems and soil cover - Almeida, Wilk Sampaio de; Carvalho, Daniel Fonseca de; Panachuki, Elói; Valim, Wander Cardoso; Rodrigues, Sonia Armbrust; Varella, Carlos Alberto Alves (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate, under simulated rainfall, the effect of soil cover on the erosion of a Typic Hapludalf erosion, in the state of Mato Grosso do Sul, Brazil, in the following crop systems: soybean, under conventional tillage; soybean, under no-tillage; established pasture, without cattle trampling; and exposed soil, as a comparison standard. Digital photographs were taken every 20 days for soil cover estimate, and 60 mm h-1 simulated rainfall was applied on the experimental plots, using a portable sprinkler infiltrometer. Soil losses, quantified every 2 min, ranged from 3.10 to 11.40 Mg ha-1, in exposed soil, and from 0.03 to 0.19 Mg ha-1, in established pasture; water losses ranged from 300 to 555 m3 ha-1, in exposed soil, and from 63 to 229 m3 ha-1, in soybean cultivation under no-tillage. Soil losses decreased with the increase in vegetation cover. In the pasture, the maximum vegetation cover was 98.10%. Conventional tillage has temporary positive effects, which makes the soil more susceptible to erosion than the conservationist systems.